Assessment of the Tendency to Use Complementary and Alternative Medicine in Patients Referring to Ahvaz Urban Pharmacies - Mohammadamin Abtahi; Sepideh Sayadi; Mandana Izadpanah; Maryam Aghakouchakzadeh (Tehran University of Medical Sciences, 2018)
Background: Complementary and alternative medicine is defined as "diagnosis, prevention, and treatment, which complements mainstream medicine by contributing to a common whole, by satisfying a demand not met by belief or by diversifying the conceptual frameworks of medicine". Alternative medicine may include acupuncture, homeopathy, phytotherapy, leech therapy, and other methods. According to the public popularity of these methods, we conducted this study to investigate the views of the public about these treatments. Methods: To perform this study, we designed a questionnaire scoring on a 10 five-point Likert scale. The goal of the study was explained to patients before filling out the questionnaire. Results: In this research, 100 cases with an average age of 30±8.47 years were studied. One percent of the studied population was uneducated, 41% had a diploma, and 58% had a university degree. Respectively, 28%, 10%, 40%, 15% of the participants expressed their confidence in Iranian traditional medicine as follows: very high, high, medium, and low, and 7% did not believe in alternative medicine. Also, 24% of respondents had used at least one of the methods of alternative medicine, like leech therapy. In addition, 33% usually and 42% sometimes used herbal tea for relieving their physical and mental illness without consulting the physician, and 25% never used it without consulting. According to the opinion of respondents, 69% believed that both modern and traditional medicine is effective, 10% expressed that modern medicine is more effective than traditional medicine, 9% were not familiar with traditional medicine, and 7% stated that traditional medicine is more effective than modern medicine. Conclusion: According to the results, most of the participants believed in alternative methods, especially along with modern medicine. For this reason, accurate and scientific education about alternative methods seems necessary for the healthcare team and the public.